Models and automation technologies for the curriculum development - V. N. Volkova; A. A. Efremov; A. V. Loginova; D. A. Kabinetskaja; M. A. Tambaum (Открытое образование (Москва), 2016)
The aim of the research was to determine the sequence of the curriculum development stages on the basis of the system analysis, as well as to create models and information technologies for the implementation of thesestages.The methods and the models of the systems’ theory and the system analysis, including methods and automated procedures for structuring organizational aims, models and automated procedures for organizing complex expertise.On the basis of the analysis of existing studies in the field of curriculum modeling, using formal mathematical language, including optimization models, that help to make distribution of disciplines by years and semesters in accordance with the relevant restrictions, it is shown, that the complexity and dimension of these tasks require the development of special software; the problem of defining the input data and restrictions requires a large time investment, that seems to be difficult to provide in real conditions of plans’ developing, thus it is almost impossible to verify the objectivity of the input data and the restrictions in such models. For a complete analysis of the process of curriculum development it is proposed to use the system definition, based on the system-targeted approach. On the basis of this definition the reasonable sequence of the integrated stages for the development of the curriculum was justified: 1) definition (specification) of the requirements for the educational content; 2) determining the number of subjects, included in the curriculum; 3) definition of the sequence of the subjects; 4) distribution of subjects by semesters. The models and technologies for the implementation of these stages of curriculum development were given in the article: 1) models, based on the information approach of A.Denisov and the modified degree of compliance with objectives based on Denisov’s evaluation index (in the article the idea of evaluating the degree of the impact of disciplines for realization of competences was used); 2) models to define the sequence of subjects from curriculum: a) the models, based on evaluating the relationship between the disciplines, using simplicial complex theory, b) the models, implemented by means of information search, using the information retrieval language with the grammar, containing the system of predicates. To implement the models, the automated dialogue procedures were developed.Models have been tested during the process of the development and the adjustment of the working curriculum for bachelor’s and master’s degree programs in the fields «System Analysis and Management», «Information Systems and Technologies», «Applied Informatics».